2004
DOI: 10.1590/s0100-879x2004000300007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a selective nonsteroidal anti-inflammatory inhibitor of cyclooxygenase-2 on the small bowel of rats

Abstract: The pathogenesis of nonsteroidal anti-inflammatory drug (NSAID) enteropathy is a complex process involving the uncoupling of mitochondrial oxidative phosphorylation and inhibition of cyclooxygenase (COX). Rofecoxib, a selective inhibitor of COX-2, has shown less gastric damage, but the same beneficial effect is not clear in the case of the small bowel. Fifty-seven male Wistar rats (250-350 g) were divided into three groups (N = 19 each) to evaluate the effect of this NSAID on the rat intestine. The groups rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Nevertheless, this cyclooxygenase inhibition does not fully explain pathogenesis of the drug-induced enteropathy. The second mechanism involves specific biochemical damage to mitochondria, with uncoupling of oxidative phosphorylation reaction and calcium release into cytosol, which in turn cause secondary biochemical damage of enterocytes resulting to increased IP (Leite et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, this cyclooxygenase inhibition does not fully explain pathogenesis of the drug-induced enteropathy. The second mechanism involves specific biochemical damage to mitochondria, with uncoupling of oxidative phosphorylation reaction and calcium release into cytosol, which in turn cause secondary biochemical damage of enterocytes resulting to increased IP (Leite et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The doses commonly used in laboratory animals, e.g., 7.5 mg . kg -1 (Leite et al, 2004), 10 mg . kg -1 (Anthony et al, 1997) or 15 mg .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have also given doses to non-fasting animals similar to our method. [17][18][19][20] Some researchers used fasted animals for dosing of NSAID. [21][22][23] We believe that the method of sacrificing by cervical dislocation without any premedication used by us is the most suitable method of sacrifice.…”
Section: Discussionmentioning
confidence: 99%
“…Hence it was reasoned that NSAID's thereby uncoupled mitochondrial oxidative phosphorylation by inducing an injurious insult on the organelle (Somasundaram et al, 1997 ). Animal studies have demonstrated mitochondrial morphological changes with the administration of pharmaceutical products such as NSAIDs (Leite et al, 2004 ).…”
Section: Mitochondria and Bacteriamentioning
confidence: 99%